SUSCETIBILIDADE DE OLERÍCOLAS A Ceratocystis fimbriata ISOLADO DE MANGUEIRA - ROSA, Caike Figueredo Fernandes; SOUZA, Eli Domingos de Oliveira; CAVALCANTI, Vittor Gomes; SANTOS, Stephany dos; MOREIRA, Cristiano; GRAICHEN, Felipe André Sganzerla (ANAIS DO ENIC, 2018)
-